COMPARISON OF BLOOD PRESSURE PARAMETERS WITH LEFT VENTRICULAR MASS IN YOUNGER MEN WITH GRADE 1 HYPERTENSION. (April 2021) - Williams, Bryan; Lacy, Peter; Jedrzejewski, Dawid; Mcfarlane, Ewan
Abstract : Objective: Non-invasive measurement of central aortic systolic pressure (CASP) has been claimed to confer advantage over conventional clinic blood pressure (BP) in predicting cardiovascular risk, particularly in younger patients where amplification is variable. This study aimed to compare relationships between clinic BP, CASP and ambulatory BP (ABPM) with left ventricular (LV) mass in younger men with grade 1 hypertension and low cardiovascular risk. Design and method: 155 men aged < 55 years with grade 1 hypertension confirmed by ABPM, underwent a cardiac magnetic resonance imaging (cMRI) scan. BP was assessed by clinic and 24-hour ABPM. CASP was evaluated using a high fidelity tonometer (BProâ) to capture radial artery waveforms calibrated to clinic systolic and diastolic or mean and diastolic (fixed form factor) and processed using a n-point moving average. LV mass indexed to body surface area (LVMI), was assessed by manual segmentation of the LV image stack acquired using a 1.5T cMRI scanner. Linear regression and receiver operator curve (ROC) analysis was used to evaluate the relationship between LVMI and BP measurement mode and whether relationships between CASP and LVMI were influenced by calibration mode. Results: In 155 men recruited from the general community (mean age 45 years) with grade 1 hypertension and low cardiovascular risk (10-year QRISKâ 5.4%), increasing BP was positively associated with LVMI. Relationships with LVMI was similar between BP measurement modes (clinic systolic BP r = 0.27, p < 0.001, 24-hour ABPM systolic BP r = 0.28 p < 0.001). The relationship of LVMI with CASP differed little for pressure waves calibrated using systolic and diastolic BP (r = 0.25, p < 0.001) or mean and diastolic BP at a form factor of 0.33 (r = 0.30, p < 0.001). ROC analysis for high LV mass detection (highest 20%), showed similar predictive value between BP modes. Conclusions: Carefully measured clinic BP confirmed by ABPM, is as good at predicting LVMI as 24-hour ABPM or CASP, irrespective of the calibration mode in younger men with grade 1 hypertension where amplification is variable. Furthermore recalibration of radial waveforms to mean and diastolic BP at a commonly used form factor (0.33) does not significantly improve this relationship.